Prairie town - Geisert, Bonnie; Geisert, Arthur (Boston : Houghton Mifflin, 1998)
Describes a year in the life of a prairie town including the effect of seasons and of economics on the ebb and flow of this agricultural community.
"Walter Lorraine books"--T.p. verso.
School Library Journal
Booklist
New York Times
5.5
K-3
Keywords: Cities and towns -- Middle West -- Juvenile literature; Prairies -- Middle West -- Juvenile literature; Country life -- Middle West -- Juvenile literature; Seasons -- Middle West -- Juvenile literature; Cities and towns; Prairies; Middle West; Country life; Seasons; Cities and towns -- Middle West; Prairies; Country life -- Middle West; Seasons; Middle West